Determinación de las características agronómicas de dos híbridos de palma aceitera y su influencia en el rendimiento - Vera Triana, Edwin Julian (2025)
The cultivation of the oil palm Elaeis guineensis originated in West Africa, with Southeast Asia currently being the largest producer. Latin America, for its part, has been increasing its planted areas thanks to the favorable agroclimatic conditions in its tropical belt. The main objective of the research was to establish the yield between OxG Amazon and Tenera oil palm hybrids (Elaeis guineensis, Jacq). In the preparation of this document, updated information was collected from scientific articles and virtual libraries, through non-experimental bibliographic research, using synthesis, analysis, and summary of the information. The conclusions determined that OxG Amazon and Tenera oil palm have agronomic differences, with the Amazon hybrid incorporating between 53-56% of oleifera palm genes that potentially affect oil yield. OxG hybrids typically have a planting density of 143 palms/ha, with growth that varies according to tree length. Factors such as environmental and agronomic conditions must be considered when selecting hybrids. Amazon hybrids have a higher investment in production costs, while the OxG hybrid, interrelated between American and African palms, has a high resistance to the bud weevil in Ecuador.